Psychologists in general hospitals: styles and collectives of thought - Santos, Fabia Monica Souza dos; Jacó-Vilela, Ana Maria (Paidéia (Ribeirão Preto), 2009)
This article aims to reflect upon the different configurations of psychologists who work in the health field, specifically in a general hospital, with a view to improve knowledge on what constitutes this professional adjustment. As a result, we indicate four collectives of thought that we judge to be the most common: Hospital Psychology, Medical Psychology, Mental Health and Health Psychology. We point some of the peculiarities of these collectives, highlighting the need of further research in which psychologists working in hospitals can narrate their histories of insertion and delimitation of the professional practice.